Julian Barnes’s The Only Story – Within and Beyond the Author’s Idiosyncrasies - Chalupský, Petr (American & British Studies Annual, 2021)
Although Julian Barnes’s fiction is diverse in its generic, stylistic and narrative metamorphoses, in terms of its subject matter it has always been preoccupied with the theme of memory, with searching for the truth of what, how and why events happened in the past. The device of an ageing person recalling his younger years or attempting to reveal the secret of another’s past can be traced throughout Barnes’s career, but it has become especially prominent in his later works, which tend to be more grim and rueful. Their narrators are almost obsessed with the meaning of their existence as they contemplate its approaching end and mortality in general. The Only Story (2018) follows this course as it is told from the perspective of a retired man retelling the story of his youthful love affair and its consequences for his subsequent life. This paper discusses how the novel thematically and stylistically follows up on his 2011 Booker Prize winner The Sense of an Ending, but also how it offers a distinct narrative which, while responding to the previous works, still comes up with an original and invigorating variant of the novel of recollection Barnes has successfully exploited before.